2009
DOI: 10.1007/s11947-009-0303-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Chickpea (Cicer arietinum L.) Seed Protein Fractions

Abstract: Proteins of ground chickpea seeds were extracted with sodium hydroxide (NaOH) solution and precipitated with addition of acid (isoelectric precipitate (C-IP)) and by cryoprecipitation (cryoprecipitate (C-CP)). The protein isolates were characterized by Native PAGE, sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), reversed-phase high performance liquid chromatography (RP-HPLC) and electrospray-ionization mass spectrometry (ESI/MS). Both the isoelectric precipitate and cryoprecipitate contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 28 publications
10
40
0
Order By: Relevance
“…Table 4 shows reported peptide sequences from the enzymatic hydrolysis of chickpea proteins. The majority of sequenced chickpea peptides are those produced from chickpea legumin, which is not surprising because legumin is the most abundant storage protein found in chickpeas (Chang, Alli, Molina, Konishi, & Boye, 2012). Sequenced peptides produced through enzymatic hydrolysis have been obtained through simulated gastrointestinal digestion with pepsin followed by pancreatin or by Properties of chickpea peptides .…”
Section: Enzymatic Production Of Peptides From Chickpea Proteinsmentioning
confidence: 99%
“…Table 4 shows reported peptide sequences from the enzymatic hydrolysis of chickpea proteins. The majority of sequenced chickpea peptides are those produced from chickpea legumin, which is not surprising because legumin is the most abundant storage protein found in chickpeas (Chang, Alli, Molina, Konishi, & Boye, 2012). Sequenced peptides produced through enzymatic hydrolysis have been obtained through simulated gastrointestinal digestion with pepsin followed by pancreatin or by Properties of chickpea peptides .…”
Section: Enzymatic Production Of Peptides From Chickpea Proteinsmentioning
confidence: 99%
“…SDS-PAGE of the protein isolates showed a distribution of molecular weights (MW) ranging from~9 tõ 80 kDa (Fig 4). Chang et al (2012) studied protein isolates from raw chickpea seeds and identified bands of~9-10,~22-24 and~39-41 kDa as legumin subunit 11S protein and those of~15,~18,~33-35 and 70 kDa as vicilin subunit 7S protein. The banding pattern of protein isolates from soaked and raw seeds was similar.…”
Section: Protein Profilementioning
confidence: 99%
“…Chickpeas are a good source of dietary protein, and its protein quality was reported to be better than other legumes Kaur & Singh, 2007). Chickpea protein is mainly composed of globulins (~56%), glutelins (~18%), albumins (~12%), prolamin (~3%) and residual proteins, and the relatively high glutelin content makes chickpea unique compared to other legumes (Chang et al, 2012). Generally, chickpeas are classified into either 'Desi' or 'Kabuli' types based primarily on seed colour and size.…”
Section: Introductionmentioning
confidence: 99%
“…Seven major protein subunits of legumin (11S) corresponding to 22.3, 24, 25.8, 37.5, 39.8, 43.5 and 43.5 kDa, and two major protein subunits of vicilin (7S) corresponding to molecular weights of 33.8 and 50.7 kDa were observed in protein isolates from lupin flour (LPPI). Previous SDS-PAGE results have shown a-subunits of legumin with molecular weight of 40.6 and 39.5 kDa and b-subunits of legumin with molecular weights of 23.5 and 22.5 kDa, and vicilin subunits with molecular weights of 70.2, 50.7, 35, 33.6, 18.9 and 15.5 kDa (Chang et al 2012;Wang et al 2010). Lupin proteins consist from three globulin proteins including 12 protein subunits of b-conglutin (7S), 4 protein subunits of a-conglutin (11S) and a minor c-conglutin (2S) of 170, 315 and 17 kDa molecular weight (Chapleau and de Lamballerie-Anton 2003).…”
Section: Resultsmentioning
confidence: 93%
“…SDS-PAGE of CPPI demonstrated four major protein subunits of legumin (11S), which correspond to molecular weights of 22.5, 22.8, 23 and 24.1 kDa and seven major protein subunits of vicilin (7S) with molecular weight of 33.7, 34.5, 37.3, 53.4, 58.4, 59.1 and 71.1 kDa. Wang et al (2010) and Chang et al (2012) have found that the globulin protein 11S (legumins) and 7S (vicilins) were the predominant major protein subunits in CPPI using isoelectric and cryoprecipitation techniques, while the 2S albumin proteins was the minor protein subunits CPPI using isoelectric and cryoprecipitation techniques. BBPI showed four major protein subunits of legumin (11S) with molecular weights of 22.4, 22.8, 23.5 and 24.2 kDa and five major protein subunits of vicilin (7S) corresponding to molecular weights of 50.7, 53.5, 55.1, 55.7 and 69.1 kDa.…”
Section: Resultsmentioning
confidence: 99%